(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Sleep is one of the most important need of humans. Approximately one-third of each person’s life is spent sleeping. Otherwise, the quality of sleep is a variable that plays very significant role in human health. Therefore, attention must always be paid to the effects of various environmental factors, including the role of waves and music, on sleep quality. The aim of this research was to examine the effect of alpha binaural waves on the sleep quality of teachers aged 40 to 50 in Rasht. For this purpose, in the initial stages of the project, a designed consent form along with the initial PSQI form was completed by a sample population of 18 individuals of both genders to assess their initial sleep quality. Based on the scores, the target population was divided into four groups. One group was given instrumental piano music as a control, while the other three groups were exposed to binaural alpha waves at frequencies of 8, 10, and 11 hertz. Then, over a 30-day period, daily forms were designed to monitor the daily performance and quality and quantity of sleep of the sample individuals after listening to the binaural waves before bedtime. These forms were completed by the sample population and evaluated daily by the team members. At the end of the 30-day period, the final PSQI form was designed to assess the sleep quality and daily performance of the study participants and was completed by them. The scores were calculated and analyzed using Microsoft Excel 2022.